1997
DOI: 10.1021/bi962316i
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Structure of the Human Pi Class Glutathione Transferase P1-1 in Complex with the Inhibitor Ethacrynic Acid and Its Glutathione Conjugate,

Abstract: The potent diuretic drug ethacrynic acid has been tested in clinical trials as an adjuvant in chemotherapy. Its target is the detoxifying enzyme glutathione transferase which is often found overexpressed in cancer tissues. We have solved the crystal structures of human pi class glutathione transferase P1-1 in complex with the inhibitor ethacrynic acid and its glutathione conjugate. Ethacrynic acid is found to bind in a nonproductive mode to one of the ligand binding sites of the enzyme (the H site) while the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 39 publications
11
106
1
3
Order By: Relevance
“…The crystal structures of both hGSTA1-1 (Cameron et al 1995) and hGSTP1-1 (Oakley et al 1997c) in complex with the diuretic drug EA and its GSH-conjugate (GS-EA) have been determined (Figure 3b,c,d ,e). These studies were among the first to demonstrate that the H-sites of the pi-and alpha-class GSTs bind similar compounds distinctly.…”
Section: Gsts In Detoxificationmentioning
confidence: 99%
“…The crystal structures of both hGSTA1-1 (Cameron et al 1995) and hGSTP1-1 (Oakley et al 1997c) in complex with the diuretic drug EA and its GSH-conjugate (GS-EA) have been determined (Figure 3b,c,d ,e). These studies were among the first to demonstrate that the H-sites of the pi-and alpha-class GSTs bind similar compounds distinctly.…”
Section: Gsts In Detoxificationmentioning
confidence: 99%
“…The three-dimensional structure of the human GST P1-1, in complex with the inhibitor ETA, implicated that the inhibitor sits in a hydrophobic pocket lined with the side chains of Tyr7, Phe8, Pro9, and Val10, while the aliphatic portions of Arg13, Val35, Ile104, and Tyr108, and the carboxylic acid moiety of the inhibitor forms a hydrogen bond to the Nε atom of Arg13. 29 Moreover, two electrostatic interactions were observed in hGST P1-1[V104] with a GSH conjugate of (+)-anti-7,8-dihydroxy-9,10-oxy-7,8,9,10-tetrahydrobenzo [α]pyrene (GSBpd), including a hydrogen bond between the hydroxyl group of Tyr7 and the sulfur atom of GSH and a direct hydrogen bond between Arg13 and the hydroxyl group of the Bpd moiety of GSBpd, demonstrating participation of Arg13 in catalysis. 13 Similarly, Bjőrnestedt et al reported mutations of the Arg15 residue (the counterpart of Arg13 in GST P1-1) in human class Alpha GST A1-1.…”
Section: S-hexylgshmentioning
confidence: 99%
“…The observation that the diagnostic GST substrate CDNB does not protect against inactivation even though KPF-SCoA is itself a GST substrate can be explained in view of some previous works. For instance, it has been reported that ethacrynic acid, both a GST inhibitor and a GST substrate, can bind to human GST P1-1 in a nonproductive and a productive mode, which suggests the existence of multiple binding sites and binding modes for GST ligands (Oakley et al, 1997). The KPF-SCoA binding mode and binding stoichiometry may thus be distinct from those of CDNB.…”
Section: Interaction Of Ketoprofen Acylated Metabolites With Gstmentioning
confidence: 99%